KESANTUNAN BERBAHASA PEMBAWA ACARA WAKTU INDONESIA TIMUR DI NET TV - Agustina, Rara Amelia; Juita, Novia (Jurnal Bahasa dan Sastra, 2019)
The purpose of this study was to describe the form of compliance and violations of the politeness in the utterances of Waktu Indonesia Timur host on NET TV. The type of this research is qualitative research by using analysis of descriptive method.The sources of this research is the utterances of Waktu Indonesia Timurhost. The findings of this study are (1) compliance with the principle of politeness in the utterances of the host in â€œWaktu Indonesia Timurâ€ was found as many as 321 data consisting of compliance oftact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim; and (2) violations of the politeness principle of language in the utterances of the host in â€œWaktu Indonesia Timurâ€ were found in 224 data consisting of violations of tact maxim, generosity maxim, approbation maxim, modesty maxim, agreement maxim, and sympathy maxim.Â Keywords: politeness,joke, Waktu Indonesia Timur